'Feeling younger, remembering better': the effect of experimentally induced subjective age on memory performance among Chinese older adults. (2nd January 2020) - Shao, Jingjin; Xiao, Luxia; Zhang, Li; Xin, Ziqiang
Abstract: Objectives: This study aimed to explore whether experimentally induced younger subjective age can lead to better memory performance among Chinese older adults. Method: A total of 203 participants aged 60–84 years were randomly assigned to three groups. In the positive and neutral feedback groups, participants were told that their memory performance was better than and equivalent to the same-aged peers after an initial memory task, respectively, in contrast to no feedback in the control group. Participants then completed a second memory measure. Results: The results revealed that participants in the positive feedback group felt younger and showed a significant increase in memory performance, whereas participants in the neutral feedback group felt older but also showed a significant increase in memory performance. For participants in the control group, no significant changes in memory performance were observed. Conclusion: It seems that experimentally induced younger subjective age can lead to better memory performance among older adults, providing a promising strategy to maintain memory functioning in old age.